HERMENEUTIK-NEGOSIASI DALAM STUDI FATWA-FATWA KEAGAMAAN: ANALISIS KRITIK TERHADAP PEMIKIRAN KHALED M. ABOU EL FADL - Muhammad Lutfi Hakim (Universitas Islam Negeri Mataram, 2020)
This paper discusses the contributions of Khaled M. Abou El Fadl in wrestling the text (al-ta’amul ma’a al-nash), which results in the implications of Islamic law. The contribution stems from his academic anxieties seeing the misogynist fatwas issued by official institutions such as the Council for Scientific Research and Legal Opinion (CRLO) in Saudi Arabia and The Society for Adherence to The Sunnah (SAS) in America. The fatwas that degrading the woman is regarded as the will of God who should not be appealed and debated. Khaled argues that the fatwa is an act of arbitrariness (despotism) and authoritarianism. By using library research and qualitative analysis, there are three results in this article. Firstly, the special group must obey the five prerequisites in order not to happen arbitrariness in interpretation and fall in authoritarianism, namely honesty, diligence, frankness, rationality, and selfrestraint. Secondly, the Qur’an competence in terms of authenticity differs from the hadith. The Qur’an is God’s authenticity. While the hadith, there are several inconsistencies that need to debate and implication on the thought of Islamic law. Thirdly, there are three elements that play a role in determining meaning in an interpretation, namely author, text, and reader. There is nothing most dominant among the three. The three relationships are given proportionally through the negotiation process, dynamic and participatory interactions in creating meaning.